Thermal and fire resistant properties of palm kernel oil and soybean oil-based polyurethanes - Wong, Chee Sien; Khairiah Haji Badri (Universiti Kebangsaan Malaysia, 2010)
Thermal and burning properties of palm kernel oil and soybean oil-based polyurethanes were compared. Monoester with hydroxyl end group was prepared by reacting the palm kernel oil (PKO) and the soybean oil (SBO) with polyhydric compound consisting of diethanolamine/ethylene glycol and potassium acetate as the catalyst. The esterification and condensation reactions were conducted with the ratio of the vegetable oils to the polyhydric compound of 80:20. The monoester was then reacted with 2, 4-diphenylmethane diisocyanate to produce the polyurethane via addition polymerization. The thermal properties were compared through differential scanning calorimetry (DSC) analysis, thermogravimetry (TGA) analysis, bomb calorimetry, dimensional stability test and fire retarding test. SBO-based polyurethane foam had lower entalphy then the PKO-based polyurethane foam with values of 7151 cal g-1 comapred to 7223 cal g-1. Similarly, the TGA analysis indicated that the percentage of weight loss of the former was also lower (91.0%) then the latter (92.3%) with stable temperatures, Tstable at 196 and 198 oC, respectively. The burning rate of the SBO-based polyurethane foam was 0.6-1.2 mm¥s-1, lower then the PKO-based polyurethane foam which was 1.1-1.6 mm s-1. However, the dimensional stability test showed that the shrinkage and expansion values were lesser for the SBO-based polyurethane foam compared to the PKO-based polyurethane.